Supraglottic laringectomy! - Čizmarevič, Bogdan (Radiology and oncology (Ljubljana), 1997)
Treatment results of two different kinds of supraglottic laryngectomies were compared. Material and methods: Treatment results of all patients treated at our department between 1st January 1990 and 31st December 1994 with partial supraglottic laryngectomy were analyzed. patients were treated with two different methods of operation - in 29 patients, the defect was reconstructed with simple suspension of the rest of larynx to the base of the tongue and, in23 patients, the defect was covered with the sternohyoid fascia. The majority of patients were postoperatively irradiated (42/52). Patients were followed for at least two years. Results: An overall 79% (41/52) local and regional control of disease was achieved. Decanulation was possible in 6% (34/52) of patients and in 85% (44/52) of patients peroral intake was achieved. locoregional control was comparable to that published in the literature, but the percentage of decanulated patients was lower. There was nostatistically significant difference in survival and function between the two methods compared. Conclusion: Since with both methods comparable results were obtained, we think that the simpler method without the use of fascia, is a more appropriate one.
Keywords: grlo; laringektomija; rak (medicina); zdravljenje